The Roman pottery district in Trier: Remarkable findings from kiln no. 5 - N. Weidner, Monika K. (Rei Cretariae Romanae Fautorum Acta, 2024)
Founded in the time of Augustus, Trier quickly developed into an influential pottery centre in the north-western Roman provinces. Already at the time when the primary settlement area of Roman trier was laid out within the marked limits the existence of pottery workshops at the north-western periphery of the town can be proven. Further kilns were added later on approximately 1 km north of the settlement area. Remains of additional pottery workshops of the late 1st to the early 2nd century were found on the other side of the river mosel. From those kiln sites mainly Gallo-Belgic ware, flagons and coarse ware have been recovered. Mainly from the middle of the 1st century onwards further pottery workshops came into existence, particularly to the south of the actual settlement where the pottery district of trier spread out. At the beginning its location was clearly outside the settlement area but the residential zone gradually expanded up to the pottery district.